1992
DOI: 10.3354/meps091037
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical and biological features of a drilling site in the North Sea, 1 year after discharges of oil-contaminated drill cuttings

Abstract: In the framework of the Paris Convention for the prevention of marine pollution, the Dutch government initiated a research programme on environmental effects of discharges of contaminated drill cuttings from platforms in the North Sea. The programme has run since 1985 and includes field surveys at drilling sites in different parts of the Dutch sector. One of the locations investigated is the former drilling site F18.9, situated on the Oyster grounds. The (abandoned) location was visited in 1988, 1 y after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…These compounds are persistent in silty anaerobic marine sediments and can cause toxic effects in marine life (Daan et al 1992;Ten Hallers et al 1994;Brouwer et al 1989;Wolfe et al 1998). Bioaccumulation is a particular phenomenon for PCBs and mercury.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds are persistent in silty anaerobic marine sediments and can cause toxic effects in marine life (Daan et al 1992;Ten Hallers et al 1994;Brouwer et al 1989;Wolfe et al 1998). Bioaccumulation is a particular phenomenon for PCBs and mercury.…”
Section: Discussionmentioning
confidence: 99%
“…The latest information on migration of the dab in the German Bight (Rijnsdorp et al 1992) is necessary for the correct interpretation of fish disease as a measure of the effects of pollution (see Vethaak 1992). Essential background information on the drilling site gradient is provided by Daan et al (1992), who describe the site and its contamination by drilling muds, and review their earlier studies which demonstrated a pollution gradient, relying on benthic ecology alone.…”
Section: Structure Of the Special Volumementioning
confidence: 99%
“…The site was located at 54O06'09"N 04"45'25"E and the transect was oriented in the direction of the residual current ( = 66"). R is the reference station 15 km NNW at 54'1 1'03"N 04O38'55"E contaminants which provided a clear gradient of biological impact on benthic community structure when studied earlier (see Daan et al 1992).…”
Section: Drilling Site Transectmentioning
confidence: 99%
See 2 more Smart Citations